Comparison of aerobic performance testing protocols in elite male wheelchair basketball players - Molik, B.; Kosmol, A.; Morgulec-Adamowicz, N.; Lencse-Mucha, J.; Mroz, A.; Gryko, K.; Marszalek, J. (Journal of Human Kinetics, 2017)
In wheelchair sports, aerobic performance is commonly assessed with the use of an arm crank ergometer (ACE), a wheelchair ergometer (WCE) or a wheelchair treadmill (WCT). There are different protocols to identify peak oxygen uptake in wheelchair sports; however, only a few protocols have been applied to evaluate these conditions in wheelchair basketball players. The purpose of this study was to compare physiological responses during maximal exercise testing with the use of ACE and WCT in wheelchair basketball players. Twelve elite male wheelchair basketball players participated in this study. The research was performed during a training camp of the Polish National Wheelchair Basketball Team. The study participants were divided into two functional categories: A (players with class 1.0 - 2.5) and B (players with class 3.0 - 4.5). Two main maximal exercise tests, i.e. wheelchair treadmill stress test (WCT test) and arm crank ergometer stress test (ACE test) were used to evaluate aerobic performance of the players. There were no statistically significant differences in aerobic tests between the players from both groups. The comparison of results achieved in two aerobic tests performed on WCT and ACE did not reveal any significant differences between the analyzed variables (peak heart rate (HRpeak), peak oxygen uptake (VO2peak), minute ventilation (VE), anaerobic threshold (AT), lactate concentration (LApeak), and a drop in lactate concentration (%LA)). Strong correlations between results achieved in WCT and ACE tests were found for VO2peak, VE and LApeak. The main conclusion of the study is that both WCT and ACE tests may be useful when determining aerobic capacity of wheelchair basketball players. Moreover, both protocols can be used by athletes regardless of their functional capabilities and types of impairment.